Thymus spp. Aqueous Extracts and Their Constituent Salvianolic Acid A Induce Nrf2-Dependent Cellular Antioxidant Protection Against Oxidative Stress in Caco-2 Cells - Carlos Martins-Gomes; Fernando M. Nunes; Amélia M. Silva (Antioxidants)
The increasing incidence of colorectal cancer and inflammatory diseases poses a major health concern, with oxidative stress playing a significant role in the onset of these pathologies. Factors such as excessive consumption of sugar-rich and fatty foods, synthetic food additives, pesticides, alcohol, and tobacco contribute to oxidative stress and disrupt intestinal homeostasis. Functional foods arise as a potential tool to regulate redox balance in the intestinal tract. Herbs (such as Thymus spp.) have long been screened for their antioxidant properties, but their use as antioxidants for medicinal purposes requires validation in biological models. In this study, we addressed the potential antioxidant protection and preventive effects of extracts from two thyme species at the intestinal level, as well as their molecular mechanisms of action. Caco-2 cells were pre-exposed (4 h) to aqueous (AD) and hydroethanolic (HE) extracts of Thymus carnosus and Thymus capitellatus, followed by a recovery period in culture medium (16 h), and then treated with tert-butyl-hydroperoxide (TBHP; 4 h), before analyzing cell viability. The effect of the extracts’ main components was also analysed. Cellular oxidative stress, cell-death markers, and the expression of antioxidant-related proteins were evaluated using flow cytometry on cells pre-exposed to the AD extracts and salvianolic acid A (SAA). Results showed that pre-exposure to AD extracts or SAA reduced TBHP-induced oxidative stress and cell death, mediated by increased levels of nuclear factor erythroid 2-related factor 2 (Nrf2) protein. The protective activity of T. capitellatus AD extract was shown to be dependent on NAD(P)H quinone dehydrogenase 1 (NQO1) protein expression and on increased glutathione (GSH) content. Furthermore, ursolic acid induced cytotoxicity and low cellular antioxidant activity, and thus the presence of this triterpenoid impaired the antioxidant effect of HE extracts. Thus, AD extracts show high potential as prophylactic dietary agents, while HE extracts arise as a source of nutraceuticals with antioxidant potential.